Prognostic significance of cyclooxygenase-2 (COX-2) and expression of cell cycle inhibitors p21 and p27 in human pleural malignant mesothelioma. Issue 5 (28th April 2004) - Baldi, A; Santini, D; Vasaturo, F; Santini, M; Vicidomini, G; Di Marino, M Pia; Esposito, V; Groeger, A M; Liuzzi, G; Vincenzi, B; Tonini, G; Piccoli, M; et al.
Abstract : Background: A study was undertaken to analyse the potential prognostic value of the immunohistochemical expression of cyclooxygenase-2 (COX-2) and p27 in 29 malignant mesotheliomas already screened for the expression of p21 and p53. Methods: Immunohistochemistry was used to determine the expression of COX-2 and p27. The correlation with survival of these factors and of p21 and p53 expression was assessed by univariate and multivariate analyses. Results: A positive statistically significant correlation was found between p27 and p21 expression (p<0.0001), but there was a negative correlation between COX-2 expression and both p27 (p = 0.001) and p21 (p<0.0001). No statistically significant correlation was recorded between p53 and all the other immunohistochemical parameters. Univariate analysis showed that overall survival was strongly influenced by p21, p27, and COX-2 expression, but multivariate Cox regression analysis showed that the only immunohistochemical parameter to influence overall survival of patients with mesothelioma was COX-2. Conclusions: These findings suggest that COX-2 expression may be a useful prognostic parameter for mesothelioma.